Prevalence of metabolic syndrome according to the presence of negative symptoms in patients with schizophrenia - Sicras-Mainar A (Dove Medical Press, 2014)
Antoni Sicras-Mainar,1 Jorge Maurino,2 Elena Ruiz-Beato,3 Ruth Navarro-Artieda4 1Badalona Serveis Assistencials SA, Badalona, Spain; 2Medical Department, Roche Farma SA, Madrid, Spain; 3Health Economics and Outcomes Research Unit, Roche Farma SA, Madrid, Spain; 4Department of Medical Information, Hospital Universitari Germans Trias i Pujol, Badalona, Spain Background: Metabolic syndrome (MetS) is one of the primary reasons for increased mortality in patients with schizophrenia. The mechanisms involved in its pathogenesis are not well understood.Objective: To estimate the prevalence of MetS in adult outpatients with schizophrenia according to the presence or absence of negative symptoms.Materials and methods: A retrospective cohort study using electronic medical records was conducted. The Positive and Negative Syndrome Scale negative-symptom factor (N1–N4, N6, G7, and G16) was used as a framework for characterizing negative symptoms. MetS was defined using the National Cholesterol Education Program Adult Treatment Panel III diagnostic criteria. An analysis of covariance model was used for correction, with significance at P<0.05.Results: One or more negative symptoms were present in 52.5% of a sample of 1,120 patients (mean age 46.8 years, men 58.4%). Dyslipidemia (48.7%), hypertension (38.2%), and diabetes mellitus (19.3%) were the most frequent comorbidities. The overall prevalence of MetS was 38.6% (95% confidence interval 35.7%–41.5%), and was significantly higher in those patients with negative symptoms (43.9% versus 34.9%, P=0.002). MetS was significantly associated with the presence of negative symptoms, age, and physical comorbidity (odds ratios 1.6, 1.2, and 1.2, respectively; P<0.05).Conclusion: A sedentary lifestyle and lack of physical exercise due to negative symptomatology may contribute to MetS development. Further studies are necessary to confirm this association and the underlying pathophysiological mechanisms. Keywords: cardiovascular risk, metabolic abnormalities, comorbidity, physical illness, schizophrenia, negative symptoms